Electrodeposition of polypyrrole/reduced graphene oxide/iron oxide nanocomposite as supercapacitor electrode material - Eeu, Yik Chong; Lim, Hong Ngee; Lim, Yee Seng; Zakarya, Salwani Asyikin; Huang, Nay Ming (Hindawi Publishing Corporation, 2013)
Polypyrrole (PPy) was reinforced with reduced graphene oxide (RGO) and iron oxide to achieve electrochemical stability and enhancement. The ternary nanocomposite film was prepared using a facile one-pot chronoamperometry approach, which is inexpensive and experimentally friendly. The field emission scanning electron microscopy (FESEM) image shows a layered morphology of the ternary nanocomposite film as opposed to the dendritic structure of PPy, suggesting hybridization of the three materials during electrodeposition. X-ray diffraction (XRD) profile shows the presence of Fe2O3 in the ternary nanocomposite. Cyclic voltammetry (CV) analysis illustrates enhanced current for the nanocomposite by twofold and fourfold compared to its binary (PPy/RGO) and individual (PPy) counterparts, respectively. The ternary nanocomposite film exhibited excellent specific capacitance retention even after 200 cycles of charge/discharge.